MICROBIOLOGICAL AND SENSORY QUALITY STATUS OF SMOKED BAUNG AND PATIN FISH MARKETED IN PASAR BAWAH PEKANBARU - Shandy Shandy; Bustari Hasan; Syahrul Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis study aimed to evaluate the microbiological and sensory quality status of smoked fish marketed in Pasar Bawah Pekanbaru. Smoked fish consisting of different types, origin of production and shelf life were sampled from three fish traders in Pasar Bawah Pekanbaru. A total of 15 samples of smoked baung fish and 15 smoked catfish representing the origin of production and shelf life were taken aseptically from the point of sale. The samples were put in sterile plastic and transported to the laboratory of the Faculty of Fisheries, Riau University, Pekanbaru to be analyzed for water content, water activity, Total Plate Number (ALT) and sensory quality (appearance, texture, odor, and taste). The average value of water content ranged between 13.44% and 25.40%, and Aw between 0.82 and 0.85. Smoked catfish was a higher water content and Aw than smoked baung fish. Smoked fish from Kampar has the highest water content and is followed by smoked fish from Langgam and Pujud. Smoked fish aged 6 days is higher than smoked fish aged 3 days. Smoked catfish has a higher ALT than smoked baung fish. Smoked fish from Kampar had the highest ALT, followed by smoked fish from Langgam and Pujud. However, the water content and ALT of smoked baung and catfish marketed at Pasar Bawah Pekanbaru still meet the SNI standard. The sensory value of smoked baung fish is higher than that of smoked catfish. Smoked fish from Pujud had the highest sensory value, followed by smoked fish from Langgam and Kampar. The sensory value of smoked fish aged 3 days was higher than smoked fish aged 6 days. Overall, the microbiological and sensory quality status of smoked baung and catfish marketed at Pasar Bawah Pekanbaru met the quality criteria set by SNI.Keywords: baung smoked, patin smoked, water content, water activity, total plate number, sensory quality